Using Remote Sensing to Detect and Map Invasive Plant Species - Everitt, J H; Yang, C; Escobar, D E; Davis, M R (Annals of Arid Zone, 2016)
Invasive exotic plant species present a serious problem to natural resource managers in the United States. This paper presents an overview on the application of aerial photography and airborne videography for detecting invasive plant species in terrestrial and aquatic environments in the United States. Ground reflectance" measurements have been used in conjunction with the studies to help determine the spectral characteristics of the plants. Season is an important variable for detecting some species because their reflectance varies at different times of the year and many species are distinguishable only when in a specific phenological stage. Computer analysis of aerial images are used to quantify weed infestations. Video imagery is integrated with global positioning system and geographic information system technologies to map noxious weed infestations. Plant species addressed include leaf)’ spurge (Euphorbia esu/a L.), saltcedar (Tamarix chinensis Lour.), waterhyacinth (Eichhornia crassipes [Mort.] Solms), hydrilla (Hydrilla verticillata [L.F.] Royle), giant salvinia (Sa/vinia mo/esta Mitchell), and giant reed (Arundo donax L.).